981. A Comprehensive Survey of Infectious Diseases Curriculum Among US Pharmacy Schools. (26th November 2018) - Jeffres, Meghan; Kufel, Wesley; Biehle, Lauren; Cho, Jonathan; Narayanan, Navaneeth; Macdougall, Conan
Abstract: Background: Pharmacists are key partners in institutional antimicrobial stewardship and require adequate knowledge and skills in antimicrobial pharmacotherapy to fulfill this role, whether or not they have specialized postgraduate training in infectious diseases (ID). The objective of this study was to describe ID topics and teaching strategies across US schools of pharmacy. Methods: A 23-question electronic survey was sent to ID faculty or curricular deans at all 137 US pharmacy schools. Results: Surveys were collected from 106 schools (77% response rate). ID curriculum was allotted 60 (IQR 40–80) hours of classroom time and primarily taught in the third year. Respondents dedicated 33% of curriculum hours to ID fundamentals and 66% to disease states. Content was primarily delivered through traditional lectures compared with active learning (75% and 25%, respectively). Greater than 94% of schools taught all tier 1 ID topics from the 2016 American College of Clinical Pharmacy Pharmacotherapy Didactic Curriculum Toolkit. Utilization of active learning methods and time allocated to ID fundamentals differed across schools. Public schools dedicated more time to antimicrobial fundamentals than private schools (40 vs. 30 hours, P = 0.023). Schools using a block schedule allotted more classroom hours to ID content than schools using semester or quarter schedules (77.5 vs. 60 vs. 50 hours, P = 0.001). Schools established less than 5 years ago devoted more classroom hours to active learning than schools established 5 to 10, 11 to 20, and greater than 20 years ago (65 vs. 25 vs. 25 vs. 20, P = 0.012). Private schools were more likely to consistently or frequently use audience response systems (86% vs. 68%, P = 0.037) and concept maps (27% vs. 6%, P = 0.005) compared with public schools. Public schools were more likely to use debates (18% vs. 2%, P = 0.006). Schools established 10 or less years ago were more likely to use concept maps (28% vs. 12%, P = 0.050), games (38% vs. 19%, P = 0.050), and simulation (41% vs. 18%, P = 0.015). Conclusion: Increased communication and collaboration between ID pharmacotherapy educators is warranted to increase consistency of ID education and distribution of educational innovations. Disclosures: All authors: No reported disclosures.